The Impact of Safety Education and Socialization Programs on Community Satisfaction at PT Jasa Raharja, Mamuju Branch - Sulvi Ardianti; Hari Yeni; Junaeda Junaeda; Muh Ferils; Abdul Wahab (Economics and Digital Business Review, 2026)
PT Jasa Raharja is a State-Owned Enterprise (SOE) whose primary duty is to provide basic protection to victims of road traffic and public transportation accidents. In addition to providing compensation, PT Jasa Raharja also plays an active role in accident prevention efforts through various safety education activities and socialization programs aimed at increasing public awareness of road safety and understanding of the services provided. PT Jasa Raharja Mamuju Branch consistently carries out safety education and socialization activities for the public, including through counseling, safety campaigns, and the provision of information regarding the rights and obligations of road users. These activities are expected to not only increase public knowledge but also impact the level of public satisfaction with the services provided by PT Jasa Raharja. Based on this, this study was conducted to analyze the effect of safety education and socialization programs on community satisfaction at PT Jasa Raharja Mamuju Branch. This research is expected to provide insight into the role and contribution of PT Jasa Raharja in improving community satisfaction and serve as evaluation material for developing future service and education programs.